Meningkatkan Efektivitas Pengangkutan Sampah melalui Penyediaan Titik Gantung Sampah di Kelurahan Sukamaju Kota Pekanbaru - Rico Purnawandi Pane; Vicky Satya Wijaksana; Aldy Adrian; Zaki Alfayed; Tiara Shifa Arizky; Dian Isla Fauziah; Puspita Sari; Anggi Aprilia Putri; Wafika Zahra; Raihan Ananda Nasfi; Muhammad Rasyid; Hizkia Hasudungan Sibagariang; Alfu Hidayatullah (Abdimas Indonesian Journal, 2026)
(1) Background: Waste management remains a critical challenge in urban areas, particularly in Pekanbaru, where waste transportation services are often hindered by narrow alleys, densely populated settlements, and steep roads that limit the accessibility of collection vehicles. (2) Purpose of the Study: This community service program aimed to optimize waste transportation through the provision of waste hanging points as temporary waste collection facilities that can be easily accessed by collection officers. (3) Methods: The program applied the Saving Matrix method to determine more efficient collection routes by considering geographical constraints and accessibility barriers. Activities were conducted through three stages, namely site identification and selection, construction of waste hanging facilities, and installation at designated locations. (4) Results: Six waste hanging points were successfully installed in strategic areas that were previously difficult to reach by waste collection vehicles. The facilities improved waste collection efficiency, reduced the need for vehicles to enter high-risk areas, minimized the potential for vehicle damage, and encouraged residents to dispose of waste in designated locations. (5) Conclusions: The provision of waste hanging points proved to be an effective and adaptive solution for overcoming accessibility challenges in waste transportation, improving service effectiveness, and supporting a cleaner and healthier environment. The program also demonstrates potential as a sustainable model for urban waste management in areas with similar characteristics.